Environmental History of Mangrove Vegetation in Pacific West-Central Mexico during the Last 1300 Years - Figueroa-Rangel, Blanca L.; Valle-Martínez, Adelina; Olvera-Vargas, Miguel; Liu, Kam-biu (Frontiers in Ecology and Evolution, 2016)
Abstract Mangroves are a highly threatened ecosystem due to climate change and human activity, which increases coastal vulnerability. Knowledge about the ecological dynamics of mangroves on a centennial timescale can reveal the different responses in vegetation, which is useful for implementing basic actions for mangrove restoration, conservation and management. A mangrove ecosystem in the Cuyutlán Lagoon area along the Pacific coast of west-central Mexico is significantly altered as a result of industrialization, salt extraction, and road construction. The long-term dynamics of the mangrove ecosystem has also been controlled by Holocene climatic variability. This study reconstructs the environmental history of mangrove vegetation around the Cuyutlán Lagoon during the last 1300 years in response to periods of human activity and climate change. The reconstruction was performed using paleoecological techniques in sediment cores that include the use of fossil pollen as a proxy for vegetation and magnetic susceptibility and geochemical data (determined by loss-on-ignition and X-ray fluorescence) as a proxy for past environmental changes. The chronology was determined using 14C dating and the age-depth model was constructed by linear interpolation. Redundancy analysis and non-metric multidimensional scaling (NMDS) were used to discern patterns of distribution of the different proxies. Results revealed that the mangrove pollen assemblage of the Cuyutlán Lagoon was dominated by the arboreal taxa Rhizophora mangle, Euphorbiaceae, Moraceae and Pinaceae, herbaceous taxa like Poaceae, Chenopodiaceae/Amaranthaceae, and aquatics such as Typhaceae and Cyperaceae. NMDS showed a clear separation between two events of human activity—the Spanish Occupation of Colima ( AD 1523-1524) and the opening of the Manzanillo port ( AD 1824-1825). Climate change events such as the Medieval Climate Anomaly (MCA) ( AD 800-1200) and the Little Ice Age (LIA) ( AD 1350-1850) were also successfully identified. The main responses were mangrove expansion (driven by R. mangle) during the LIA and the Manzanillo Port Opening, while the MCA was a highly perturbed period marked by multiple hurricane events and low or no pollen deposition in the sediment. During the Spanish Occupation, the aquatic taxa Typhaceae expanded together with an increase in Ca, Sr and carbonate contents.